2014
DOI: 10.1631/jzus.b1400073
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin D and severity of liver fibrosis in chronic hepatitis C patients: a systematic meta-analysis

Abstract: Abstract:To conduct a systematic review of group studies assessing the association of serum vitamin D status with the severity of liver fibrosis in chronic hepatitis C patients using meta-analysis. The relevant research literatures were identified by searching PubMed and EMBASE databases prior to October 2013 with no restrictions. We included group studies that reported odds ratio (OR) estimates with 95% confidence intervals (CIs) or a mean with standard deviation (SD) for the association between serum vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…Older and more recent research has investigated the link between vitamin D homeostasis and bone loss in patients with liver disease [ 7 , 8 , 22 , 46 ]. Vitamin D deficiency in chronic liver disease is only partly the result of a synthesis dysfunction of the liver or/and decreased vitamin D absorption caused by intestinal edema due to portal hypertension or to cholestasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older and more recent research has investigated the link between vitamin D homeostasis and bone loss in patients with liver disease [ 7 , 8 , 22 , 46 ]. Vitamin D deficiency in chronic liver disease is only partly the result of a synthesis dysfunction of the liver or/and decreased vitamin D absorption caused by intestinal edema due to portal hypertension or to cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…HCV and HIV infections are both associated with increased levels of proinflammatory cytokines that can promote osteoclastogenesis or inhibit osteoblast differentiation and collagen synthesis [ 7 , 8 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant inverse relationship between the severity of inflammatory fibrosis and cirrhosis and serum 25(OH)D 3 levels was observed in HCV patients [32,33,37,40,[62][63][64]. This implies VD deficiency as an independent predictor and risk factor for inflammatory liver complications in HCV patients [38,39,[65][66][67]. VD deficiency was also associated with reduced hepcidin expression, mixed cryoglobulinemia, and hepatic encephalopathy in HCV patients [41][42][43].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 99%
“…11,12 Nearly 200 million people worldwide are chronically infected with hepatitis C which could lead to the development of cirrhosis, end stage liver disease, hepatocellular carcinoma and liver transplantation. 13 role in progression of liver disease severity especially of chronic hepatitis C. 14 It has been suggested that many patients of chronic liver disease have insufficient serum level of 25 OH vitamin D. 15…”
Section: Introductionmentioning
confidence: 99%